2021
DOI: 10.3389/fsurg.2021.670123
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Yun-Type Optimized Pelvic Floor Training Therapy for Middle-Aged Women With Severe Overactive Bladder: A Randomized Clinical Trial

Abstract: Background: This study aimed to evaluate the clinical efficacy of Yun-type optimized pelvic floor training therapy for middle-aged women with severe overactive bladder (OAB).Methods: This randomized, observer-blinded, parallel-group controlled clinical trial included 108 middle-age women with severe OAB and assigned them to the intervention group (treated with combination of Yun-type optimized pelvic floor training with solifenacin for 12 weeks) and control group (treated with solifenacin for 6 weeks and, afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Other studies indicated that training in a standing position can induce higher pelvic floor muscle activity level than that in the lying position 13 . With a standing position, the pelvic floor muscle training can be incorporated with dancing components to allow training more enjoyable, engaging, and thus better compliance to attain better training effects 14 . The combination of pelvic tilt and twist in dance-integrated training can stretch and activate the pelvic floor muscles 15 17 , including the groin, perineum, waist, abdomen, chest, and arm muscles 14 , 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies indicated that training in a standing position can induce higher pelvic floor muscle activity level than that in the lying position 13 . With a standing position, the pelvic floor muscle training can be incorporated with dancing components to allow training more enjoyable, engaging, and thus better compliance to attain better training effects 14 . The combination of pelvic tilt and twist in dance-integrated training can stretch and activate the pelvic floor muscles 15 17 , including the groin, perineum, waist, abdomen, chest, and arm muscles 14 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…With a standing position, the pelvic floor muscle training can be incorporated with dancing components to allow training more enjoyable, engaging, and thus better compliance to attain better training effects 14 . The combination of pelvic tilt and twist in dance-integrated training can stretch and activate the pelvic floor muscles 15 17 , including the groin, perineum, waist, abdomen, chest, and arm muscles 14 , 18 . Such rhythmic/music training movement can also exploit the coordination of surrounding muscles, including the rectus abdominis, hip adductor, and gluteus maximus muscles 15 .…”
Section: Introductionmentioning
confidence: 99%